Mould Contamination of Fish and Fish Products with a Special Reference to its Public Health Significance: A Review - Darwish, Wageh; Mohamed, Alaa S.E.; Abdallah, Karima M.E. (Journal of Advanced Veterinary Research, 2023)
Fish and fish products represent major contributors to supply humans with part of their needs of the essential amino acids, vitamins, minerals, omega -3-fatty acids, and other needed micronutrients. However, fish and fish products are highly perishable foods that can easily spoiled and decomposed, possibly because of its cross contamination from the surrounding environment. Fish attracts a vast array of microorganisms, of these; mould and yeast represent a major sector of these microbiota, which by turn van lead to rapid decomposition of fish or even produce several toxicological implications if ingested. In this review, we will highlight the available literature about mould contamination of fish and fish products with a special reference to its public health significance.